First results from SPIFFI. I: The Galactic Center - Horrobin, M; Eisenhauer, F; Tecza, M; Thatte, N; Genzel, R; Abuter, R; Iserlohe, C; Schreiber, J; Schegerer, A; Lutz, D; Ott, T; Schodel, R (2004)
In this and a companion paper (Eisenhauer et al. 2003b), we discuss some of the scientific results obtained during the SPIFFI guest instrument runs at the VLT in March and April 2003. This paper concentrates on results for the Galactic Center. Section I discusses the stellar population of the Galactic Center, in which we clearly detect, for the first time, an early, hot WN star, as well as a large number of WC stars. Analysis of the stellar population indicates that the young stars in the Galactic Center originated in a high metalicity starburst about 5 Myr ago. A surprising result is that essentially all young stars in the central 10" belong to one of two well defined, rotating stellar rings/disks. Section 2 outlines a new determination of the distance to the Galactic Center which is essentially free of systematic uncertainties in the astrophysical modelling, and gives R. as 7.94 +/- 0.42 kpc.